Satyamaya jīvana, athavā, Satyāsatya vicāra - Mashruwala, Kishorlal Ghanshyamlal, 1890-1952 (SAMP early 20th-century Indian books project, 1935)
On the concept of compromise in ethics; based on "On compromise" by John Morley, 1838-1923.